On Socio-economic Roles and Specialization - Robert P. Gilles; Emiliya Lazarova; Pieter H.M. Ruys (Tinbergen Institute, 2006)
Xiaokai Yang's theory of economic specialization under increasing returns to scale is a formal development of the fundamental Smith-Young theorem on the extent of the market and the social division of labor. In this theory specialization and, thus, the social division of labor is firmly embedded within a system of perfectly competitive markets. This leaves unresolved whether and how such development processes are possible in economies based on more primitive, non-market organizations. In this paper we discuss a general relational model of economic interaction. Within this non-market environment we discuss the emergence of economic specialization and eventually of economic trade and a social division of labor. We base our approach on three levels in organizational development: the presence of a stable relational structure; the presence of relational trust and subjective specialization; and, finally, the emergence of objective specialization through the institution and the social recognition of economic roles.
Keywords: D02; O12; 330; Economic development; social division of labor; non-market economies.